Improved performance of polyvinylidenefluoride-hexafluorpropylene based nanocomposite polymer membranes containing lithium bis(oxalato)borate by phase inversion for lithium batteries - Aravindan, Vanchiappan (2011)
Nanocomposite polymer electrolyte membranes were prepared by phase inversion technique in polyvinylidenefluoride-hexafluoropropylene (PVdFeHFP) matrix. These membranes were gelled with 0.5 M LiBOB in EC:DEC (1:1 v/v). These gel polymer membranes (GPMs) were incorporated with nanoparticles of AlO(OH)n and prepared composite polymer membranes (CPMs) also. The a.c. impedance analysis shows that AlO(OH)n filled membrane exhibits conductivity of 1.82 x 10^-3 S cm^-1 at ambient temperature.